Clarification of acid site location in MSE-type zeolites by spectroscopic approaches combined with catalytic activity: comparison between UZM-35 and MCM-68. Issue 7 (3rd February 2022) - Toyoda, Hiroto; Osuga, Ryota; Wang, Yong; Park, Sungsik; Yazawa, Koji; Gies, Hermann; Gilbert, Christopher J.; Yilmaz, Bilge; Kelkar, C. P.; Yokoi, Toshiyuki
Abstract : Difference in the acid site location of MSE-type zeolites between UZM-35 and MCM-68 was clarified by the spectroscopic approaches combined with the catalytic activity. Abstract : MSE-type zeolites synthesized by different organic structure-directing agents (OSDAs), UZM-35 and MCM-68, were prepared. The location of Brønsted acid sites derived from the framework Al atoms and acidic properties were investigated based on 27 Al MQMAS NMR and in situ IR techniques combined with the evaluation of the catalytic activity. We have successfully found a significant difference in the location of Brønsted acid sites in the MSE-type framework; 61 and 33% of acid sites were located at the 12-ring channel for MCM-68 and UZM-35, respectively. The differences in the location of the acid sites yielded their unique catalytic activities for the hydrocarbon cracking reactions, indicating that a well-chosen type of OSDAs for the synthesis is one of the possibilities for controlling the distribution of the framework Al atoms in the MSE-type framework.